2017
DOI: 10.1016/j.physleta.2017.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of another semimetallic silicene allotrope with Dirac fermions

Abstract: Materials with Dirac point are so amazing since the charge carriers are massless and have an effective speed of light. Among the reported two-dimensional silicon allotropes, no one showing such exciting nature was proved experimentally. This fact motivates us to search for other such two-dimensional silicon allotropes. As a result, a new single atomic layer thin silicon allotrope was predicted by employing CALYPSO code in this work. This silicon allotrope is composed of eightmembered rings linked by Si-Si bond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 27 publications
5
37
1
Order By: Relevance
“…Liu et al theoretically demonstrated that different from planar T-graphene, buckled T-graphene possess Dirac-like fermions and high Fermi velocity [12,13], while Huang et al claimed that buckled T-graphene is a normal metal as planar T-graphene [14]. Also, it was theoretically proposed that 2D tetragonal allotrope of Si (Tsilicene) is stable and is nodal line semimetal [15]. Inspired by the experimental investigations for atomic structure of grain boundaries in single layer 1H-MoS 2 [16], a tetragonal allotrope of single layer MX 2 (M=Mo, W, Nb; X=S, Se, Te) [17][18][19][20][21], which consists of repeated square and octagon rings, was theoretically predicted.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al theoretically demonstrated that different from planar T-graphene, buckled T-graphene possess Dirac-like fermions and high Fermi velocity [12,13], while Huang et al claimed that buckled T-graphene is a normal metal as planar T-graphene [14]. Also, it was theoretically proposed that 2D tetragonal allotrope of Si (Tsilicene) is stable and is nodal line semimetal [15]. Inspired by the experimental investigations for atomic structure of grain boundaries in single layer 1H-MoS 2 [16], a tetragonal allotrope of single layer MX 2 (M=Mo, W, Nb; X=S, Se, Te) [17][18][19][20][21], which consists of repeated square and octagon rings, was theoretically predicted.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogenated 2D tetragonal silicene (g-SiH) is stable that has been reported previously. 14 So next we just discuss the stability of a-SiH and b-SiH by calculating the binding energy, phonon dispersions and AIMD simulations. The binding energy for hydrogenated 2D tetragonal silicene dened by…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8] Several two-dimensional (2D) allotropes of silicene have been proposed, such as MoS 2 -type silicene, 9 tetra-silicene, 10 trigonal dumbbell silicene, honeycomb dumbbell silicene, large honeycomb dumbbell silicene, [11][12][13] and tetragonal silicone. 14,15 The physical properties in these materials mainly stem from the symmetry of the crystal structure. So, it is highly desirable to study 2D allotropes of materials with different symmetries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 First-principles calculations have proposed that the 2D tetragonal allotrope of Si is a nodal line semimetal, and hydrogenation could induce a semimetal-semiconductor transition in this silicene allotrope. 8 Also, 2D tetragonal Ge and tetragonal Sn are theoretically predicted to be nodal line semimetals which are identied by nontrivial Z 2 invariant and topological edge states at the sample boundaries. 9 Additionally, some tetragonal graphenelike analogues, such group V elements, XBi (X ¼ Si, Ge, Sn) and TMDs, have also been proposed and predicted to be stable.…”
Section: Introductionmentioning
confidence: 99%